Meningkatkan Kualitas dan Kuantitas Pertanyaan dan Pernyataan Peserta Didik Melalui Problem Based Learning pada Pelajaran Biologi - Tami, Luh Putu; Probosari, Riezky Maya; Widoretno, Sri (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2019)
This research aims to increase the quality and quantity of student’s question and statement through the application of Problem-Based Learning model on the biology subject. The research is conducted into 3 cycles with the research object of the students grade XI MIA 3 State High School 2 of Surakarta in the school year of 2015/2016. The result of observation at pre-cycle shows the question and statement is that appears 1 question and 16 statements. The quality of question and statement is in the knowledge dimension of factual C1. Based on the result of observation, shows the low quality and quantity of the student’s question and statement, thus it needs to increase by applying the Problem-Based Learning model.This research is included as a Classroom Action Research (CAR) which consists of 3 activity cycles. The collecting data are conducted by observing, interviewing, and documenting. To validate the data is used the techniques of triangulation and descriptive qualitative analysis. The data analysis of the quality of the question and statement is used the revised Taxonomy Bloom. The quantitative data analysis of the question and statement is based on the appeared amounts. The result of the research shows the quality of the question at cycles of I,II, and III sequentially detected FC1, FC3, FC4, KC1, KC2; FC1, FC2, KC1, KC2, KC3, PC2; KC2, PC2, MC2. And, in the statement sequentially FC1, FC2, KC1, KC2, KC4, PC2; FC1, FC2, KC1, KC2; FC1, FC2, FC3, KC2, KC4, PC2. The quantity of the question at cycles of I,II, and III sequentially as much as 27, 28, dan 17. Meanwhile in the statement sequentially 71, 81, 90. The conclusion of this research is that the quality and quantity of student’s question and statement through the application of Problem-Based Learning model which varies in each cycle is increased.